Lactic acid production from food waste at an anaerobic digestion biorefinery: effect of digestate recirculation and sucrose supplementation - Bühlmann, Christopher H.; Mickan, Bede S.; Tait, Stephan; Batstone, Damien J.; Bahri, Parisa A. (Frontiers in Bioengineering and Biotechnology, 2023)
Low lactic acid (LA) yields from direct food waste (FW) fermentation restrict this production pathway. However, nitrogen and other nutrients within FW digestate, in combination with sucrose supplementation, may enhance LA production and improve feasibility of fermentation. Therefore, this work aimed to improve LA fermentation from FWs by supplementing nitrogen (0-400 mgN·L-1) as NH4Cl or digestate and dosing sucrose (0-150 g·L-1) as a low-cost carbohydrate. Overall, NH4Cl and digestate led to similar improvements in the rate of LA formation (0.03±0.02 and 0.04±0.02 h-1 for NH4Cl and digestate, respectively), but NH4Cl also improved the final concentration, though effects varied between treatments (5.2±4.6 g·L-1). While digestate altered the community composition and increased diversity, sucrose minimised community diversion from LA, promoted Lactobacillus growth at all dosages, and enhanced the final LA concentration from 25-30 g·L-1 to 59-68 g·L-1, depending on nitrogen dosage and source. Overall, the results highlighted the value of digestate as a nutrient source and sucrose as both community controller and means to enhance the LA concentration in future LA biorefinery concepts.